The future is present in the past: A meta‐analysis on the longitudinal associations of parent–adolescent relationships with peer and romantic relationships. Issue 1 (25th August 2022) - Schulz, Susanne; Nelemans, Stefanie; Hadiwijaya, Hana; Klimstra, Theo; Crocetti, Elisabetta; Branje, Susan; Meeus, Wim
Abstract: Positive peer and romantic relationships are crucial for adolescents' positive adjustment and relationships with parents lay the foundation for these relationships. This longitudinal meta‐analysis examined how parent–adolescent relationships continue into later peer and romantic relationships. Included longitudinal studies ( k  = 54 involving peer relationships, k  = 38 involving romantic relationships) contained demographically diverse samples from predominantly Western cultural contexts. Multilevel meta‐regressions indicated that supportive and negative parent–adolescent relationships were associated with supportive and negative future peer and romantic relationships. Meta‐analytic structural equation modeling ( k  = 54) indicated that supportive parent–adolescent relationships unidirectionally predicted supportive and negative peer relationships, while negative parent–adolescent relationships were bidirectionally associated with supportive and negative peer relationships. Maintaining mutually supportive relationships with parents may help adolescents to develop positive social relationships.